Formulation and Antioxidant Test of Gotu Kola Leaf Ethanol Extract Cream (Centella asiatica) - adminagus adminagus; Vani Febri Rosiana; Maulita Saraswati; Wahyu Purwanjani (Yayasan Citra Dharma Cindekia, 2023)
Cosmetic products in the form of cream preparations containing antioxidant compounds have been developed to prevent premature aging of the skin. One of these plants is the gotu kola plant which can be used as a source of natural antioxidants. The active compounds contained in gotu kola leaves are flavonoids, alkaloids, saponins, tannins, triterpenoids, terpenoids which have been developed into dosage forms suitable for cream products. To determine the formulation of gotu kola leaf extract cream as an antioxidant. This research is experimental research. This experiment is based on extraction, formulation, preparation evaluation tests including organoleptic, pH, homogeneity, viscosity, spreadability, adhesive power. Then an antioxidant test was carried out. Statistical analysis was carried out using the ANOVA method. The research results show that gotu kola leaf extract can be formulated into cream preparations with various base variations that meet the requirements for good preparation evaluation. The antioxidant test results showed the IC50 FI value was 34.04 ppm, F2 30.27 ppm, F3 26.43 ppm. Statistical test results show significant antioxidant value, namely <0.05.